Linkage analysis and integrated software GAPL for pure-line populations derived from four-way and eight-way crosses - Zhang, Luyan; Meng, Lei; Wang, Jiankang (Elsevier, 2019)
Pure lines derived from multiple parents provide abundant variation for genetic study. However, efficient genetic analysis methods and user-friendly software are still lacking. In this study, we developed linkage analysis methods and integrated analysis software for pure-line populations derived from four-way and eight-way crosses. First, polymorphic markers are classified into different categories according to the number of identifiable alleles in the inbred parents. Expected genotypic probability is then derived for each pair of complete markers, and based on them a maximum likelihood estimate (MLE) of recombination frequency is calculated. An EM algorithm is proposed for calculating recombination frequencies in scenarios that at least one marker is incomplete. A linkage map can thus be constructed using estimated recombination frequencies. We describe a software package called GAPL for recombination frequency estimation and linkage map construction in multi-parental pure-line populations. Both simulation studies and results from a reported four-way cross recombinant inbred line population demonstrate that the proposed method and software can build more accurate linkage maps in shorter times than other published software packages. The GAPL software is freely available from www.isbreeding.net and can also be used for QTL mapping in multi-parental populations.